2016
DOI: 10.1039/c6lc00910g
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial flow regulates the angiogenic response and phenotype of endothelial cells in a 3D culture model

Abstract: A crucial yet ill-defined phenomenon involved in the remodeling of vascular networks, including angiogenic sprouting, is flow-mediated endothelial dynamics and phenotype changes. Despite interstitial flow (IF) being ubiquitously present in living tissues surrounding blood capillaries, it is rarely investigated and poorly understood how endothelial cells respond to this flow during morphogenesis. Here we develop a microfluidic 3D in vitro model to investigate the role of IF during vasculogenic formation and ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
165
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 187 publications
(191 citation statements)
references
References 49 publications
5
165
1
1
Order By: Relevance
“…It is noteworthy that we observed endothelial sprouting with the direction of TVF and interstitial flow. Numerous studies using other microfluidic models have reported that angiogenic sprouts preferentially form against the direction of interstitial flow (Song and Munn, 2011;Song et al, 2012;Vickerman and Kamm, 2012;Kim et al, 2016). However, these previous studies were done with HUVECs, which are venous microvascular ECs, in contrast to our study using MAECs, an arterial endothelial cell type.…”
Section: Discussionmentioning
confidence: 62%
“…It is noteworthy that we observed endothelial sprouting with the direction of TVF and interstitial flow. Numerous studies using other microfluidic models have reported that angiogenic sprouts preferentially form against the direction of interstitial flow (Song and Munn, 2011;Song et al, 2012;Vickerman and Kamm, 2012;Kim et al, 2016). However, these previous studies were done with HUVECs, which are venous microvascular ECs, in contrast to our study using MAECs, an arterial endothelial cell type.…”
Section: Discussionmentioning
confidence: 62%
“…Besides the basic components required, the type of method or device used can have a large impact on the outcome of experiments. For instance, not having control over the interstitial flow can already result in different sprouting behaviour [21] or in false gradients [71]. Choosing a suitable system depends on the process and effect that is targeted in the research; a practical approach is to first generate an understanding of the in vivo process and deduct what the main factors are, as has been outlined in this review.…”
Section: Discussionmentioning
confidence: 99%
“…This also applies to branching as additional tip cells can emerge from an existing sprout [20]. The sprouts follow gradients of chemotactic factors like VEGF, Semaphorins, and Ephrins as well as physical forces from interstitial flow, strain, and matrix stiffness ( Figure 2B3) [9,11,16,18,[21][22][23][24]. During sprout formation, the inside of these sprouts open up, forming a lumen that can be perfused from the original vessel.…”
Section: Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies using microfluidic platform have been reported that recreate the 3D context of each aspect of the TME and metastasis in vitro. [10][11][12][13] However, to our knowledge, no versatile in vitro experimental model that reconstitutes direct interplay between constituents of the TME during tumorigenesis has yet been reported. Here we describe a biomimetic TME model to mimic the complex inter actions of the tumor, stromal, and endothe lial cells, all of which are essential components of the TME that hinder the effective treatment of cancers.…”
mentioning
confidence: 99%